Evaluation of Epidemiological Data of Malaria Between 2001-2011 in Sanliurfa, Turkey - Doni, Nebiye Yentur; Zeyrek, Fadile Yildiz; Seyrek, Adnan; Simsek, Zeynep; Gurses, Gulcan; Topluoglu, Seher (Ankara Microbiology Soc, 2016)
Although Plasmodium vivax is the only cause of malaria cases detected in Turkey, an increase number of imported P.falciparum cases have begun to be observed recently. Sanliurfa is a province located at Southeastern region of Turkey where malaria is endemic and also one of the two largest malaria epidemics of Turkey was experienced with 84.345 cases in 1994. As this region has borders with countries like Iraq, Iran and Syria, cross border migration caused an increase in imported cases. In addition, climate change, alteration in temperature and humidity due to the Southeastern Anatolian Irrigation Project have led an increase in suitable breeding grounds for mosquitoes. Since new indigenous malaria cases, except imported ones are not detected in Sanliurfa nowadays, there is not enough data on the malaria epidemiology in this region including recent years. The aim of this study was to evaluate the epidemiological data in connection with malaria cases observed in Sanliurfa which is a critical region for this infection for a 11-year-period, between the years of 2001 to 2011, retrospectively. Data obtained from the Malaria Control Unit of the Communicable Diseases Division of Sanliurfa Provincial Health Directorate were analized in terms of frequency of the cases, distribution of the cases in years and months, demographical characteristics, the source and species distribution of the parasite and the locations of the disease. A total of 1.149.196 blood smear samples have been examined during 11-year-period as part of surveillance programme and 4394 (0.4%) of them were positive for Plasmodium spp. The agent was P.vivax in 99.9% (4391/4394) of the cases, while in three cases (0.07%) who were diagnosed after 2010, it was P.falciparum. Of the patients 2351 (53.5%) were male and 2043 (46.5%) were female (p> 0.05), whose age ranging from 3 months to 80 years (mean age: 19.21 +/- 16.12 years). The frequencies of the cases according to the age groups 0-11 months, 1-4 years, 5-9 years, 10-14 years and a 15 years were as follows; 2.5%, 15.1%, 18%, 13.9% and 50.5%, respectively. The detection of Plasmodium spp. in the samples examined in 2002 (1244/110.533; 1.1%) was the highest, and in 2011 (1/50.981; 0.002%) was the lowest. The distribution rates of 4394 cases according to the years between 2001 to 2011, were found as 25.4%, 28.3%, 17.8%, 10.9%, 8.9%, 5.6%, 1.4%, 1.4%, 0.2%, 0.009% and 0.02%, respectively. Of all cases, 80.6% were autochthonous and 19.4% were imported. Most of the cases were detected in Siverek county with a rate of 71.4%, followed by Ceylanpinar (13.5%) and Viransehir (6.6%) counties. Although malaria cases were detected throughout the year in Sanliurfa in respect to the climate, the highest numbers were recorded in September (832/4394; 18.9%) and November (1054/4394; 24%). This study emphasized that malaria cases due to local transmission declined to zero in Sanliurfa like the recent situation in Turkey. However, P.falciparum malaria cases are being reported due to the travels to endemic countries or migrations from those countries. Effective malaria control attempts, within the scope of Malaria Elimination Programme implemented in Turkey, should be continued with the same stability without any abruption in Sanliurfa province where the disease had been endemic in the past.
Şanliurfa'da 2001-2011 Yillarina Ait Sitma Epidemiyolojik Verilerinin Degerlendirilmesi
Keywords: Malaria; Plasmodium; epidemiology; Turkey